VD_FINDINFO HC / 2010 / 372 vom 5. Juli 2010 - VD Tribunal cantonal (2010)
ACTION EN PARTAGE SUCCESSORAL, SUCCESSION, MESURE PROVISIONNELLE, JURIDICTION GRACIEUSE, URGENCE | 604 CC, 452 al. 1 CPC, 489 CPC, 496 al. 2 CPC, 499 al. 2 let. a CPC, 586 CPC